“Kristendommens absolutte status”: Religionsteologien hos Ernst Troeltsch - Jørgensen, Jonas Adelin (Dansk Teologisk Tidsskrift, 2014)
The contribution of E. Troeltsch towards a modern Protestant theology of religions takes its point of departure in the conundrum of Christianity as (theologically) absolute and (historically) relative religion. The article describes the background for Troeltsch’s theology, his analysis of other religious traditions, and his theological reflections based on his approach informed by the ‘Religionsgeschichtliche Schule’. The article argues for a development in Troeltsch’s theology of religions from a fairly common liberal protestant hierarchical view to a much more relativistic understanding. Troeltsch’s contribution is contextualized and placed in the larger modern discussion on the relationship between Christianity as a historical phenomenon, its relation to other religious traditions, and the specific content of Christianity and its claim to truth. In conclusion, the article characterizes Troeltsch’s theology of religions as an act of balancing between a methodological or epistemological relativism and a more holistic relativism, which is the very possible dead-end of metaphysical thinking